Method for preparing amorphous silicon nanowire material by using metal salt mixed silicon waste and application of amorphous silicon nanowire material
By mixing metal salt with silicon waste and growing amorphous silicon nanowires on a carbon substrate using Joule thermal shock technology, the problem of attenuation of the negative electrode of the toxic catalyst and lithium-ion battery in the prior art is solved, and efficient and stable Preparation of lithium-ion battery negative electrode material has commercial practical value.
Patent Information
- Application Number
- CN202411443516.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The existing amorphous silicon nanowire preparation methods use toxic silanes or expensive catalysts, which limits the large-scale application of lithium-ion battery negative electrode materials, and the silicon-based negative electrode will lead to solid electrolyte interface during lithium alloying/dealloyation. The reconstruction of the membrane and lithium ion consumption lead to attenuation of the electrode performance.
Using metal salt and silicon waste, amorphous silicon nanowires are grown in situ on the carbon substrate through Joule thermal shock technology. Using metal salt as a catalyst avoids the use of toxic substances and expensive precursors, and achieves rapid and simple preparation. process.
The prepared amorphous silicon nanowire material exhibits more stable electrochemical performance in the negative electrode of lithium-ion battery, avoids the formation of lithium dendrites, improves the safety and performance stability of the battery, and has commercial practical value.
Smart Images

Figure CN119306222A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing amorphous silicon nanowire material by using metal salt mixed with silicon waste and application thereof, belonging to the technical field of lithium ion batteries. Background Art
[0002] Developing renewable energy is an urgent task today, and solar energy is considered to be the best alternative to fossil energy. In recent years, the solar photovoltaic industry has been a rapidly growing sunrise industry, with an annual global growth rate of up to 35%. It is estimated that by 2050, solar power generation will reach 25% of the global total demand. The rapid growth of the industry is driving the demand for silicon wafers, and nearly 30% to 40% of cutting silicon waste will be generated during the cutting and preparation process of silicon wafers. Remelting cutting silicon waste to recover crystalline silicon is extremely challenging, and some secondary impurities may also be introduced when removing impurities generated during the cutting process. It is worth noting that the conversion of cutting silicon waste into high-value new silicon-based negative electrode materials for lithium-ion batteries has attracted widespread attention.
[0003] However, the silicon-based negative electrode will expand / contract in volume (>300%) during the lithium alloying / de-alloying process, which will cause the continuous reconstruction of the solid electrolyte interface (SEI), irreversibly consume more and more lithium ions, and eventually lead to the electrode material performance attenuation or even failure. One-dimensional silicon nanowires can withstand huge stress without breaking, and have unique advantages such as fast ion / electron transfer rate, and are considered to be one of the promising structural designs. In addition, compared with crystalline silicon, amorphous silicon has isotropic strain / stress, higher resistance to structural fracture, and the reaction potential of amorphous silicon with lithium (~0.22V) is higher than that of crystalline silicon (~0.12V), which can inhibit the formation of lithium dendrites and improve the safety of the battery.
[0004] At present, there have been a lot of research works on the preparation methods of amorphous silicon nanowires, such as chemical etching, thermal evaporation deposition, chemical vapor deposition (CVD) and supercritical fluid-liquid-solid synthesis (SFLS), etc. However, these methods use toxic silane or expensive catalysts and complex instruments, which limits the potential for large-scale applications, especially for lithium-ion battery negative electrode materials.
[0005] Therefore, upgrading the large amount of high-value cut silicon waste generated by the photovoltaic industry into a practical amorphous silicon nanowire material and using it as the negative electrode of lithium-ion batteries is a new way to realize the resource utilization of photovoltaic silicon waste. Summary of the invention
[0006] In order to solve the problems existing in the current preparation process of amorphous silicon nanowires, one of the purposes of the present invention is to provide a method for preparing amorphous silicon nanowire materials by using metal salt mixed with silicon waste. The method uses photovoltaic cutting silicon waste as raw material and metal salt as catalyst. The two are mixed and attached to a carbon substrate. The silicon waste is liquefied by Joule heat shock and then grown in situ on the substrate to form amorphous silicon nanowire materials. The specific preparation method is as follows:
[0007] (1) A metal salt is dissolved in a solvent to obtain solution I.
[0008] (2) Adding silicon waste to solution I obtained in step (1), and uniformly dispersing by ultrasonication to obtain a mixed slurry of metal salt and silicon waste.
[0009] (3) The carbon substrate is immersed in the mixed slurry obtained in step (2), stirred, taken out and vacuum dried to obtain a carbon substrate with metal salt and silicon waste attached thereto.
[0010] (4) The carbon substrate with attached metal salt and silicon waste obtained in step (3) is loaded on a reaction table of a Joule thermal shock device, and the power is turned on to obtain an amorphous silicon nanowire material grown on the carbon substrate after reaction.
[0011] Preferably, in step (1), the metal salt is one or more of copper salt, iron salt, zinc salt, silver salt, cobalt salt, nickel salt and manganese salt mixed in any proportion; wherein the mass percentage of the metal salt in solution I is 0.5% to 10%.
[0012] Preferably, in step (1), the solvent is one or more of deionized water, ethanol, ethylene glycol, methanol, acetone, and ethyl acetate mixed in any proportion.
[0013] Preferably, in step (2), the silicon waste is generated during the photovoltaic cutting of silicon ingots; wherein the mass percentage of the silicon waste in the mixed slurry is 3% to 15%.
[0014] Preferably, in step (2), the ultrasonic dispersion time is 5 min to 30 min.
[0015] Preferably, in step (3), the carbon substrate is any one of carbon cloth, carbon felt, graphite paper, carbon fiber, and carbon film.
[0016] Preferably, in step (3), the stirring time is 10 min to 120 min, the vacuum drying temperature is 60 to 100° C., and the time is 6 to 24 h.
[0017] Preferably, in step (4), the reaction temperature of the Joule thermal shock device is 1000-3000° C., and the reaction time is 0.5-5 s.
[0018] The second purpose of the present invention is to provide an application of the prepared amorphous silicon nanowire material in the negative electrode material of lithium ion batteries.
[0019] Beneficial effects of the present invention
[0020] (1) The present invention provides a novel method for preparing amorphous silicon nanowire materials, wherein the waste silicon cut materials are mixed with metal salts, the metal salts are used as catalysts, and transient heating is performed in combination with Joule thermal shock. The waste silicon attached to the carbon substrate is decomposed and fused with the metal salt precursor, and further grown in situ into amorphous silicon nanowires. The diameters of the silicon nanowires obtained by adding different metal salts are also different.
[0021] (2) The amorphous silicon nanowire material prepared by the present invention can be directly used as the negative electrode of a lithium-ion battery. Compared with traditional crystalline silicon nanowires or crystalline silicon negative electrode materials, the prepared amorphous silicon nanowires can obtain more stable electrochemical properties.
[0022] (3) Compared with the conventional growth and preparation of amorphous silicon nanowires, the method disclosed in the present invention is short-range and fast, does not require complicated processes or expensive and toxic precursors, and has great commercial value. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a schematic diagram of amorphous silicon nanowires prepared by Joule thermal shock in the present invention.
[0024] Figure 2 is a SEM picture of the cut silicon waste used in Example 1.
[0025] Figure 3 This is a SEM picture of the silicon waste used in Example 1 mixed with metal salt and attached to the carbon cloth after drying.
[0026] Figure 4 is a SEM picture of the amorphous silicon nanowire material obtained in Example 1.
[0027] Figure 5 This is the TEM image of the amorphous silicon nanowire material obtained in Example 1 ( Figure 5 (A)) and selected area electron diffraction (SAED) images ( Figure 5 (B)).
[0028] Figure 6 The graph is a graph of the first 100 cycle performance and the corresponding coulomb efficiency when the amorphous silicon nanowire material obtained in Example 1 is used as the negative electrode of a lithium-ion battery.
[0029] Figure 7 This is the TEM image of the crystalline silicon nanowire material obtained in Comparative Example 1 ( Figure 7 (A)) and SAED images ( Figure 7 (B)). DETAILED DESCRIPTION
[0030] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following embodiments are only simple examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0031] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0032] Example 1
[0033] This embodiment provides a method and application of preparing amorphous silicon nanowire material by using metal salt mixed with silicon waste, including the following steps:
[0034] (1) Weigh 2.0 g of copper sulfate and dissolve it in 100 mL of deionized water and stir to obtain Solution I.
[0035] (2) Weigh 5.0 g of cut silicon waste and disperse it in solution I obtained in step (1), disperse it by ultrasonication for 20 min, and then stir and mix it for 30 min to obtain a uniform mixed slurry.
[0036] (3) Cut the carbon cloth into small pieces (~1×5 cm) and put them into the mixed slurry obtained in step (2) to fully soak them. Take them out after 15 minutes and vacuum dry them at 80°C for 12 hours to obtain a carbon substrate with metal salts and silicon waste attached.
[0037] (4) The carbon cloth substrate with attached metal salt and silicon waste obtained in step (3) is loaded on the reaction table of the Joule thermal shock equipment, the temperature is controlled at 1800° C., and the reaction time is set to 1.0 s to obtain an amorphous silicon nanowire material grown on the carbon substrate.
[0038] The diameter of the amorphous silicon nanowire material prepared in this embodiment is measured to be 10-15 nm.
[0039] Scanning electron microscope (JSM-7800) was used to test the amorphous silicon nanowire material prepared by mixing the cut silicon waste and the silicon waste attached to the carbon cloth with metal salt under the above conditions. The test results are as follows: Figure 2 , Figure 3 , Figure 4 As shown in the picture, it can be seen that the silicon waste raw material is in the form of hundreds of nanometers of fragments, which can be evenly dispersed with metal salts and attached to the carbon cloth. After the Joule thermal shock reaction, dense silicon nanowire materials are obtained.
[0040] Transmission electron microscopy (JEM-2100F) was used to test the crystal structure of the silicon nanowire material prepared under the above conditions. The test results are shown in Figure 5 As shown in the picture, it can be seen that the prepared nanowire material has an amorphous structure and no obvious diffraction fringes appear.
[0041] The amorphous silicon nanowire material on the carbon cloth substrate prepared in Example 1 was directly used as the negative electrode of the lithium ion battery, with a metal lithium sheet as the counter electrode, Celgard2325 as the separator, and 1 mol / L LiPF6 (the solvent is a mixture of dimethyl carbonate and ethylene carbonate in a volume ratio of 1:1) as the electrolyte. The button battery was assembled in an argon-protected glove box using a CR2032 button battery shell. The charge and discharge test was carried out with a test current of 0.2-0.8A / g and a voltage charge and discharge range of 0.01-3.0V. The charge and discharge cycle performance was as follows: Figure 6 As shown in the picture, it can be seen that the first coulombic efficiency is greater than 90%, and the reversible capacity is stabilized at 2400mAh / g after 100 cycles, showing excellent electrochemical cycle performance.
[0042] Example 2
[0043] This embodiment provides a method and application of preparing amorphous silicon nanowire material by using metal salt mixed with silicon waste, including the following steps:
[0044] (1) Weigh 0.5 g of silver nitrate and dissolve it in 100 mL of ethanol solution and stir evenly to obtain solution I.
[0045] (2) Weigh 5.0 g of cut silicon waste and disperse it in solution I obtained in step (1), disperse it by ultrasonication for 20 min, and then stir and mix it for 30 min to obtain a uniform mixed slurry.
[0046] (3) Cut the carbon cloth into small pieces (~1×5 cm) and put them into the mixed slurry obtained in step (2) to fully soak them. Take them out after 15 minutes and vacuum dry them at 80°C for 12 hours to obtain a carbon substrate with metal salts and silicon waste attached.
[0047] (4) The carbon cloth substrate with attached metal salt and silicon waste obtained in step (3) is loaded on a Joule thermal shock equipment reaction table, the temperature is controlled at 1900° C., and the reaction time is set to 1.0 s to obtain an amorphous silicon nanowire material grown on the carbon substrate.
[0048] The diameter of the amorphous silicon nanowire material prepared in this embodiment is measured to be 5-10 nm.
[0049] Other properties are similar to those of the material prepared in Example 1.
[0050] Example 3
[0051] This embodiment provides a method and application of preparing amorphous silicon nanowire material by using metal salt mixed with silicon waste, including the following steps:
[0052] (1) Weigh 10 g of ferric nitrate and dissolve it in 100 mL of a mixed solution of ethylene glycol and methanol and stir well to obtain solution I.
[0053] (2) Weigh 5.0 g of cut silicon waste and disperse it in solution I obtained in step (1), disperse it by ultrasonication for 20 min, and then stir and mix it for 30 min to obtain a uniform mixed slurry.
[0054] (3) Cut the carbon cloth into small pieces (~1×5 cm) and place them into the mixed slurry obtained in step (2) to fully soak them. Take them out after 15 minutes; vacuum dry them at 80°C for 12 hours to obtain a carbon substrate with attached metal salts and silicon waste.
[0055] (4) The carbon cloth substrate with attached metal salt and silicon waste obtained in step (3) is loaded on the reaction table of the Joule thermal shock equipment, the temperature is controlled at 1700° C., and the reaction time is set to 1.0 s to obtain an amorphous silicon nanowire material grown on the carbon substrate.
[0056] The diameter of the amorphous silicon nanowire material prepared in this embodiment is measured to be 1-5 nm.
[0057] Other properties are similar to those of the material prepared in Example 1.
[0058] Example 4
[0059] This embodiment provides a method and application of preparing amorphous silicon nanowire material by using metal salt mixed with silicon waste, including the following steps:
[0060] (1) Weigh 3.0 g of nickel nitrate and dissolve it in 100 mL of acetone solution and stir evenly to obtain solution I.
[0061] (2) Weigh 3.0 g of cut silicon waste and disperse it in solution I obtained in step (1), disperse it by ultrasonication for 20 min, and then stir and mix it for 30 min to obtain a uniform mixed slurry.
[0062] (3) Cut the carbon cloth into small pieces (~1×5 cm) and put them into the mixed slurry obtained in step (2) to fully soak. Take them out after 15 minutes and vacuum dry them at 80°C for 12 hours;
[0063] (4) The carbon cloth substrate with attached metal salt and silicon waste obtained in step (3) is loaded on the reaction table of the Joule thermal shock equipment, the temperature is controlled at 1800° C., and the reaction time is set to 1.5 s to obtain an amorphous silicon nanowire material grown on the carbon substrate.
[0064] The diameter of the amorphous silicon nanowire material prepared in this embodiment is measured to be 15-20 nm.
[0065] Other properties are similar to those of the material prepared in Example 1.
[0066] Example 5
[0067] This embodiment provides a method and application of preparing amorphous silicon nanowire material by using metal salt mixed with silicon waste, including the following steps:
[0068] (1) Weigh 3.0 g of cobalt nitrate and dissolve it in 100 mL of ethyl acetate solution and stir evenly to obtain solution I.
[0069] (2) Weigh 15.0 g of cut silicon waste and disperse it in solution I obtained in step (1), disperse it by ultrasonication for 20 min, and then stir and mix it for 30 min to obtain a uniform mixed slurry.
[0070] (3) Cut the carbon cloth into small pieces (~1×5 cm) and put them into the mixed slurry obtained in step (2) to fully soak them. Take them out after 15 minutes and vacuum dry them at 80°C for 12 hours to obtain a carbon substrate with metal salts and silicon waste attached.
[0071] (4) The carbon cloth substrate with attached metal salt and silicon waste obtained in step (3) is loaded on the reaction table of the Joule thermal shock equipment, the temperature is controlled at 2300° C., and the reaction time is set to 2.0 s.
[0072] The diameter of the amorphous silicon nanowire material prepared in this embodiment is measured to be 25-30 nm.
[0073] Example 6
[0074] This embodiment provides a method and application of preparing amorphous silicon nanowire material by using metal salt mixed with silicon waste, including the following steps:
[0075] (1) Weigh 3.0 g of manganese nitrate and dissolve it in 100 mL of deionized water and stir to obtain Solution I.
[0076] (2) Weigh 5.0 g of cut silicon waste and disperse it in solution I obtained in step (1), disperse it by ultrasonication for 20 min, and then stir and mix it for 30 min to obtain a uniform mixed slurry.
[0077] (3) Cut the carbon cloth into small pieces (~1×5 cm) and put them into the mixed slurry obtained in step (2) to fully soak them. Take them out after 15 minutes and vacuum dry them at 80°C for 12 hours to obtain a carbon substrate with metal salts and silicon waste attached.
[0078] (4) The carbon cloth substrate with attached metal salt and silicon waste obtained in step (3) is loaded on the reaction table of the Joule thermal shock equipment, the temperature is controlled at 2500° C., and the reaction time is set to 3.0 s to obtain an amorphous silicon nanowire material grown on the carbon substrate.
[0079] The diameter of the amorphous silicon nanowire material prepared in this embodiment is measured to be 30-50 nm.
[0080] Other properties are similar to those of the material prepared in Example 1.
[0081] Comparative Example 1
[0082] For comparison, the difference between this comparative example and Example 1 is that no metal salt is used, and the preparation method is the same as that of Example 1, and the specific steps are as follows:
[0083] (1) Weigh 5.0 g of cut silicon waste and dissolve it in 100 mL of deionized water solution and stir it evenly. After ultrasonic dispersion for 20 min, stir and mix it for 30 min to obtain a uniform slurry.
[0084] (2) Cut the carbon cloth into small pieces (~1×5 cm) and put them into the slurry obtained in step (1) to fully soak them. Take them out after 15 minutes; vacuum dry them at 80°C for 12 hours to obtain a carbon substrate with silicon waste attached.
[0085] (3) The carbon cloth substrate with silicon waste attached thereto in step (2) is loaded onto a Joule thermal shock equipment reaction table, the temperature is controlled at 1800° C., and the reaction time is set to 1.0 s.
[0086] The diameter of the crystalline silicon nanowire material prepared in this embodiment is measured to be 5-15 nm.
[0087] Transmission electron microscopy (JEM-2100F) was used to test the crystal structure of the crystalline silicon nanowire material prepared under the above conditions. The test results are shown in Figure 7 As shown, it can be seen that the prepared nanowires are crystalline silicon nanowires. Further electrochemical performance tests show that the first coulombic efficiency is about 85%, and the reversible capacity is less than 1500 mAh / g after 100 cycles at a current of 0.8 A / g, and the capacity stability is much lower than that of the amorphous silicon nanowires prepared in Example 1.
[0088] Comparative Example 2
[0089] This comparative example provides a method and application of preparing crystalline silicon nanowire material using silicon waste, comprising the following steps:
[0090] (1) Weigh 5.0 g of cut silicon waste and dissolve it in 100 mL of deionized water solution and stir it evenly. After ultrasonic dispersion for 20 min, stir and mix it for 30 min to obtain a uniform slurry.
[0091] (2) Cut the carbon cloth into small pieces (~1×5 cm) and put them into the slurry obtained in step (1) to fully soak them. Take them out after 15 minutes and vacuum dry them at 80°C for 12 hours to obtain a carbon substrate with silicon waste attached.
[0092] (3) The carbon cloth substrate with silicon waste attached obtained in step (2) is loaded on the reaction table of the Joule thermal shock equipment, the temperature is controlled at 1900° C., and the reaction time is set to 2.0 s.
[0093] The diameter of the crystalline silicon nanowire material prepared in this embodiment is measured to be 30-40 nm.
[0094] The material prepared in this comparative example was further subjected to electrochemical performance tests, and the first coulombic efficiency was about 78%. After 100 cycles at a current of 0.8 A / g, the reversible capacity was less than 1350 mAh / g, and the capacity stability was much lower than that of the amorphous silicon nanowires prepared in Example 1.
[0095] The above contents are further detailed descriptions of the present invention in combination with specific implementation methods, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention.
Claims
1. A method for preparing amorphous silicon nanowire material by using metal salt mixed with silicon waste, characterized in that: The method comprises the following steps: (1) dissolving a metal salt in a solvent to obtain a solution I; (2) adding silicon waste to solution I obtained in step (1), stirring after ultrasonic dispersion, to obtain a mixed slurry of metal salt and silicon waste; (3) fully soaking the carbon substrate in the mixed slurry obtained in step (2), taking it out and vacuum drying it to obtain a carbon substrate with metal salt and silicon waste attached; (4) The carbon substrate with attached metal salt and silicon waste obtained in step (3) is loaded on a reaction table of a Joule thermal shock device, and the power is turned on to obtain an amorphous silicon nanowire material grown on the carbon substrate after reaction.
2. The method for preparing amorphous silicon nanowire material by using metal salt mixed with silicon waste according to claim 1, characterized in that: In step (1), the metal salt is one or more of copper salt, iron salt, zinc salt, silver salt, cobalt salt, nickel salt and manganese salt mixed in any proportion; wherein the mass percentage of the metal salt in solution I is 0.5% to 10%.
3. The method for preparing amorphous silicon nanowire material by using metal salt mixed with silicon waste according to claim 1, characterized in that: In step (1), the solvent is one or more of deionized water, ethanol, ethylene glycol, methanol, acetone, and ethyl acetate mixed in any proportion.
4. The method for preparing amorphous silicon nanowire material by using metal salt mixed with silicon waste according to claim 1, characterized in that: In step (2), the silicon waste is generated during the photovoltaic silicon ingot cutting process; wherein the mass percentage of the silicon waste in the mixed slurry is 3% to 15%.
5. The method for preparing amorphous silicon nanowire material by using metal salt mixed with silicon waste according to claim 1, characterized in that: In step (2), the ultrasonic dispersion time is 5 min to 30 min; the stirring time is 10 min to 120 min.
6. The method for preparing amorphous silicon nanowire material by using metal salt mixed with silicon waste according to claim 1, characterized in that: In step (3), the carbon substrate is any one of carbon cloth, carbon felt, graphite paper, carbon fiber, and carbon film.
7. The method for preparing amorphous silicon nanowire material by using metal salt mixed with silicon waste according to claim 1, characterized in that: The vacuum drying temperature in step (3) is 60° C. to 100° C., and the drying time is 6 h to 24 h.
8. The method for preparing amorphous silicon nanowire material by using metal salt mixed with silicon waste according to claim 1, characterized in that: In step (4), the reaction temperature of the Joule thermal shock device is 1000-3000° C., and the reaction time is 0.5-5 s.
9. Use of the amorphous silicon nanowire material prepared by the method of any one of claims 1 to 8 in negative electrode materials for lithium-ion batteries.
Citation Information
Patent Citations
Method for preparing silicon carbide nanowire by adopting metallic nickel or amorphous carbon lamination
CN103058193A
Silicon nanowire-based flexible self-supporting electrode material and preparation method thereof
CN115036496A
Method for preparing silicon nanowire cluster material from silicon waste and application of silicon nanowire cluster material
CN118419935A
Silicon nanowire, silicon nanowire structure and method for producing the same, and nonaqueous electrolyte secondary battery
JP2015020921A
Process for the growth of amorphous Silicone Oxidenanowires directly from NiO / Si and nanowires made fromthe process
KR1020060027968A